Grief and growth among Chinese parents who lost their only child: the role of positive and negative experiences of social support from different sources. Issue 1 (31st December 2022) - Zhou, Ningning; Sun, Yue; She, Zhuang; Xu, Xin; Peng, Yanan; Liu, Xinyang; Xi, Juzhe
ABSTRACT: Background: In China, bereaved parents who have lost their only child are known as Shidu parents, and they tend to present high levels of prolonged grief reactions. To date, a widespread focus has been placed on positive social support, while potential negative experiences have been relatively neglected. Additionally, the role of social support from different sources (i.e. close family members [partner, siblings, grandchildren], peers, and others [relatives, friends, colleagues]) has not been examined thoroughly. Objective: The present study investigated whether social support from different sources has a differential impact on postloss adaptation (i.e. prolonged grief and growth). The loss-orientated and restoration-orientated coping strategies of the dual process model were also tested for their mediating roles. Methods: A total of 277 Chinese Shidu parents were recruited to complete a series of questionnaires including social support from different sources, prolonged grief symptoms, posttraumatic growth, and dual process coping strategies. Correlation analyses, paired sample t tests and structural equation modelling were conducted. Results: More positive support were related to less prolonged grief symptoms and more posttraumatic growth, while more negative support was only related to more prolonged grief. Positive support from close family members and others was significantly related to prolonged grief/growth, and negative support from these sources was significantly positively associated with prolonged grief. Positive or negative support from people who shared a similar experience was unrelated to prolonged grief/growth. Positive and negative support were related to prolonged grief and growth through loss-oriented coping strategies. Conclusion: Overall, the present study indicated that positive and negative support experiences from different sources functioned differently in the recovery of Chinese Shidu parents and that loss-oriented coping played a mediating role. These findings highlight the importance of differentiating social support by traits in coping with grief and the crucial mediating role of loss-oriented coping. HIGHLIGHTS: More positive support correlated with less prolonged grief and more growth, while more negative support correlated with more prolonged grief. Support from family members and friends was more potent than that from peers. Social Support correlated with prolonged grief/growth through loss-oriented coping.